2021
DOI: 10.1007/s10151-021-02432-9
|View full text |Cite
|
Sign up to set email alerts
|

A mapping review of sacrococcygeal pilonidal sinus disease

Abstract: Background Pilonidal sinus is a hole in the natal cleft which may cause severe pain and become infected. The evidence base for management of pilonidal sinus is said to be poor quality, poorly focused and rapidly proliferating. We undertook a systematic mapping review to provide a broad overview of the field and support the identification of research priorities. Methods We searched MEDLINE, CINAHL, and EMBASE from inception to 22nd Nov 2020 for primary rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The endoscopic method has the advantage of treating the tracts under vision in contrast to pit picking or laser treatment. In their mapping review on PD, Kumar et al claimed the need for trials comparing minimally invasive procedures with standard care [9]. The authors also confirmed and highlighted the absence of clear, front‐running surgical interventions for PD and the presence in the literature of a great heterogeneity in the definition, measurements and clinical outcomes, as pointed out in a recent systematic review [17].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The endoscopic method has the advantage of treating the tracts under vision in contrast to pit picking or laser treatment. In their mapping review on PD, Kumar et al claimed the need for trials comparing minimally invasive procedures with standard care [9]. The authors also confirmed and highlighted the absence of clear, front‐running surgical interventions for PD and the presence in the literature of a great heterogeneity in the definition, measurements and clinical outcomes, as pointed out in a recent systematic review [17].…”
Section: Discussionmentioning
confidence: 93%
“…Similar 'snapshot' have already been taken at a national level. For instance, 983 studies from the literature on the management of PD were the object of a recent mapping review by Kumar et al [9], summarizing eight decades of research on the topic. A total of 36 studies were systematic reviews with/ without meta-analyses, 121 randomized controlled trials and 826 observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive treatments include curettage, laser therapy, endoscopic adjuvant therapy, and radiofrequency ablation (Fig. 13 ) 51 . Although there are many surgical treatment options, the most appropriate surgical treatment for PS disease remains controversial 52 , 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Pilonidal sinus is a chronic sinus or cyst that causes clinical symptoms such as hair, ulceration and discharge, swelling, and pain in the lesion and is commonly located in the soft tissue of the sacrococcygeal intergluteal fissure. 1 The disease occurs in young men over the age of 17. 2 In China, the incidence of pilonidal sinus is relatively low compared with Europe and the United States, but in recent years, the incidence of the sacrococcygeal pilonidal sinus has been on the rise.…”
Section: Introductionmentioning
confidence: 99%
“…Pilonidal sinus is a chronic sinus or cyst that causes clinical symptoms such as hair, ulceration and discharge, swelling, and pain in the lesion and is commonly located in the soft tissue of the sacrococcygeal intergluteal fissure 1 . The disease occurs in young men over the age of 17 2 .…”
Section: Introductionmentioning
confidence: 99%